Stress corrosion cracking of the slip-ring connectors of a 2 MW wind turbine. (November 2022) - Ramírez, Edgar I.; Figueroa, Carlos G.; Romero, Jorge L.; Ramos, E.; Schouwenaars, Rafael; Ortiz, A.
Highlights: The slip ring showed a fine fracture in a connector to the windings. The insulating varnish of the component showed severe deterioration. Failure was by transgranular stress corrosion cracking in OFHC copper. Design details and small manufacturing defects contribute to failure. A varnish protecting the parts from atmosphere may prevent this failure. Abstract: The failure of the connectors between the slip ring and rotor of a 2 MW wind turbine was investigated. Visual inspection, low magnification stereomicroscopy and scanning electron microscopy showed the presence of highly branched transgranular cracks. The cracks are in zones of increased stress, as demonstrated by finite elements. The observations show that the failure is caused by stress corrosion cracking (SCC). Fourier transform infrared spectroscopy (FTIR) was used to characterise the insulating varnish of the slip ring. Tropical climate conditions cause the wetting of the components and with a close-by livestock plant is a source of NH3 contamination. Corrections to the design and manufacturing process of the slip rings were suggested to increase the life expectancy of the generator, although the selection of an insulating varnish with higher resistance to environmental exposure is probably the most efficient manner to reduce the incidence of this phenomenon in the future.